2019
DOI: 10.1002/adts.201900057
|View full text |Cite
|
Sign up to set email alerts
|

Spin Logic Gates Operated by Protonation and Magnetism in Molecular Combinational Circuits

Abstract: The protonation and magnetism effects on the spin transport properties of benzo[b]phenazine (BPE) and bis(o-phenylenediamine) manganese (IV) complex (Mn-OPD) molecules in series and in parallel are theoretically investigated using density functional theory (DFT) combined with nonequilibrium Green's function method (NEGF). The spin-resolved currentvoltage curves show that the magnetic field mainly regulate the spin-polarized direction of current, and the protonation effect will significantly reduce the magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In order to explain the NDR effect in the I–V curves of zISNs systems, the bias‐dependent transmission spectra of M4 and M5 model devices with bias voltage from 0 to 1.0 V are plotted in Figure a and b, respectively. The Landauer–Büttiker formula has been employed to calculate the current when a voltage bias Vb is applied between L and R electrodes, with μR=eVb/2 and μL=eVb/2 assumed . In the bias‐dependent transmission spectrum, the chemical potentials of the left and right electrodes are separated by the bias and distributed evenly around the EF.…”
Section: Resultsmentioning
confidence: 99%
“…In order to explain the NDR effect in the I–V curves of zISNs systems, the bias‐dependent transmission spectra of M4 and M5 model devices with bias voltage from 0 to 1.0 V are plotted in Figure a and b, respectively. The Landauer–Büttiker formula has been employed to calculate the current when a voltage bias Vb is applied between L and R electrodes, with μR=eVb/2 and μL=eVb/2 assumed . In the bias‐dependent transmission spectrum, the chemical potentials of the left and right electrodes are separated by the bias and distributed evenly around the EF.…”
Section: Resultsmentioning
confidence: 99%
“…We note that theoretical calculations have proposed that protonation is capable of modulating the spin transport properties of specific molecules and the combined implementation of pH and magnetic field could modulate the direction and intensity of spin–polarized current. 27,84,85 These works hold promise for new observations to be made in protonation-controlled single molecule spin transport under magnetic fields.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular transistors, discussed so far, have not been accompanied by any evidence of nonvolatile switching at room temperature: the device measurement were carried out at temperatures below 30 K. To obtain molecular spintronic devices functional, operational at temperatures closer to room temperature route, the molecular systems exhibiting a robust spin transition have begun to attract increasing attention [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The spin crossover phenomenon, representing transitions between two distinguishable spin states, occurs in a large variety of 3d transition metal molecular compounds [30,31] [62], if this can be demonstrated reliably at room temperature. Zhang et al [63] showed that for spin crossover molecular films of [Fe(H2B(pz)2)2bipy],…”
Section: Molecular Spin Transistor Using Spin Crossover Molecular Thin Filmsmentioning
confidence: 99%